Total Body Photography and Sequential Digital Dermoscopy in Pregnant Women - Martins-Costa, Gabriela M. (Dermatol Pract Concept, 2019)
BACKGROUND: Melanocytic nevi can vary in size and number in pregnant women, and the differential diagnosis with melanoma may be challenging. OBJECTIVES: To describe changes in total body photography of pregnant women and dermoscopy aspects of their nevi. METHODS: A prospective cohort study with 703 melanocytic nevi from 18 women was performed, comparing them in the first and third trimester of pregnancy. Images were analyzed between the 2 periods for changes in dermoscopic aspects. RESULTS: Total body photography images indicated that 44% of patients had new lesions. Regarding the observed changes, there were symmetric or regular changes of the network (23% of cases), occurrence of new globules/dots (12.4%), new vascular structures (3.2%), new streaks (1.7%), and new structureless area (1.0%). Moreover, 55.0% of the nevi increased in size. Enlarging of the nevi was observed mostly on the abdomen (87.1%; P < 0.001) and showed more network changes (27.1%; P = 0.014) and formation of new globules and dots (16.0%; P < 0.001). Patients with a risk of developing melanoma presented more frequently enlarged nevi (45%; P = 0.019). The association between streak formation and skin type was significant (P = 0.012) and was more frequent in skin type II (2.7%), when compared with skin types III (1.3%) and IV (0%). CONCLUSIONS: Development of new melanocytic nevi may occur in pregnant women. The majority of the preexisting melanocytic nevi showed enlarging, and most of them presented with benign dermoscopic changes. The appearance of new streaks is more frequent in fair skin types. Patients with a personal or family history of melanoma in first-degree relatives presented more nevi with changes in size.